PERAN UNIT PELAYANAN PEREMPUAN DAN ANAK DALAM PENERAPAN PRINSIP RESTORATIVE JUSTICE PADA TINDAK PIDANA DENGAN PELAKU ANAK DI MAKASSAR - Nanang Ardiansyah; Sitti Aisyah; Asni (Qadauna: Jurnal Ilmiah Mahasiswa Hukum Keluarga Islam, 2022)
Abstract The subject of this research is the role of the PPA Unit in the application of the principles of Restorative Justice in criminal acts with child offenders in Makassar. This research is a field research using syar'i, theological and normative juridical approaches. The results of this study indicate that in the implementation of Restorative Justice the PPA Unit Polrestabes Makassar only acts as a mediator and facilitator. There are two driving factors for the PPA Unit, namely internal factors including the integrity and capability of the PPA Unit and external factors including collaboration between the PPA Unit and related agencies to facilitate the application of Restorative Justice principles in case resolution. The view of Islamic law relating to Restorative Justice is in line with Islamic teachings because basically the concept of Restorative Justice places more emphasis on solving problems in a family manner. The PPA unit should carry out studies and education related to the principles of Restorative Justice to the community so that cases of child crimes can be resolved amicably. The PPA Unit must also improve the understanding and capability of the PPA Unit apparatus by holding training on case resolution based on the principles of Restorative Justice. Keywords: Children, Restorative Justice, Crime.